The complete bipartite graphs which have exactly two orientably edge-transitive embeddings - Yu, Xue (Ars mathematica contemporanea, 2020)
In 2018, Fan and Li classified the complete bipartite graph ?$K_{m, n}$? that has a unique orientably edge-transitive embedding. In this paper, we extend this to give a complete classification of ?$K_{m, n}$? which have exactly two orientably edge-transitive embeddings.
Keywords: bipartite graphs; dvodelni grafi; edge-transitive embeddings; povezavno tranzitivne vložitve